UTILIZATION OF GENERATIVE AI IN GREEN WORK ENVIRONMENT SIMULATION FOR WORK INTEGRATED LEARNING PROGRAM BASED ON ENVIRONMENTALLY FRIENDLY INDUSTRY IN VOCATIONAL EDUCATION INSTITUTIONS - Suputra, I Nyoman; Basuki, Andi; Dharma, Buyung Adi; Gunawan, Ari; Syaifruddin, Afis Baghiz (Branding: Jurnal Manajemen dan Bisnis, 2025)
The development of artificial intelligence technology, particularly Generative Artificial Intelligence (AI), presents new opportunities for innovative learning methods in vocational Education. This study aims to utilise Generative AI in creating a green work environment simulation as a learning medium for Work-Integrated Learning (WIL), with a focus on environmental and eco-friendly industries. This simulation is designed to provide an in-depth and interactive learning experience while strengthening students' competence in applying sustainability principles and green work practices in the industrial world. The research method employed is an experiment involving the development of a Generative AI-based simulation prototype that integrates elements of a green work environment, including waste management, energy efficiency, and the utilisation of renewable resources. The research participants were vocational program students who participated in Work-Integrated Learning (WIL). The evaluation was conducted by measuring the increase in understanding of the concept of green industry and the practical skills acquired through simulation. The study's results showed that the use of Generative AI-based simulation significantly increased students' learning motivation, theoretical understanding, and practical skills compared to conventional learning methods. In addition, this simulation also facilitates the development of soft skills, such as decision-making and problem-solving, in the context of green work. Thus, the use of Generative AI in green work environment simulations makes a positive contribution to improving the quality of environmentally friendly industry-based Work-Integrated Learning (WIL) Programs in vocational Education institutions. This study offers recommendations for vocational Education institutions to adopt AI technology, supporting adaptive, innovative, and sustainable learning processes that produce a competent and environmentally conscious workforce.